Biological and Morphometric Characteristics of Spodoptera litura (Fabricius) on Soybean under Laboratory Conditions - Chowdary, Kota Sahithi; Harika, Repaka; Katlam, B.P. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2024)
Bionomics studies of Spodoptera litura (Fabricius) were conducted in the laboratory with soybean as host to study the morphological characters at different stages in its life cycle. Keeping this in view, this study was conducted during 2022-23 at laboratory, Dept. of Entomology, Indira Gandhi Krishi Vishwavidyalaya, Raipur (C.G.). From studies it was found that eggs were spherical in shape and yellowish creamy in colour. First instar larva was pale green in colour and fully grown larva changed to dark blackish brown colour with larval period of 15.7 ± 1.34 days. Pupae were dark reddish brown and pupal period lasted for 7.2 ± 0.63 days. The adult moth was brown in colour with a complex pattern of creamish white coloured crisscross markings on the forewings and silvery white hindwings with longevity of 6.5 ± 0.53 days in male, 7.1 ± 0.32 days in female and total life cycle was completed in 32.7 ± 1.32 days. Morphometric studies were also conducted and found that the diameter of egg was 0.43 ± 0.02 mm. Fully grown larva was about 35.85 ± 1.57 mm in length and 4.32 ± 0.15 mm in width. Pupa was having 14.84 ± 0.83 mm length and 4.11 ± 0.23 mm width. The female moth had body length of 16.20 ± 1.03 mm and wing span of 32.97 ± 1.39 mm whereas, male moth had body length of 15.30 ± 1.16 mm and wingspan of 32.11 ± 0.92 mm.